The Exopolysaccharide Cepacian Plays a Role in the Establishment of the Paraburkholderia phymatum – Phaseolus vulgaris Symbiosis - Liu, Yilei; Bellich, Barbara; Hug, Sebastian; Eberl, Leo; Cescutti, Paola; Pessi, Gabriella (Frontiers in Microbiology, 2020)
Paraburkholderia phymatum is a rhizobial strain that belongs to the beta-proteobacteria, a group known to form efficient nitrogen-fixing symbioses within root nodules of several legumes, including the agriculturally important common bean. The establishment of the symbiosis requires the exchange of rhizobial and plant signals such as lipochitooligosaccharides (Nod factors), polysaccharides, and flavonoids. Inspection of the genome of the competitive rhizobium P. phymatum revealed the presence of several polysaccharide biosynthetic gene clusters. In this study, we demonstrate that bceN, a gene encoding a GDP-D-mannose 4,6-dehydratase, which is involved in the production of the exopolysaccharide cepacian, an important component of biofilms produced by closely related opportunistic pathogens of the Burkholderia cepacia complex (Bcc), is required for efficient plant colonization. Wild-type P. phymatum was shown to produce cepacian while a bceN mutant did not. Additionally, the bceN mutant produced a significantly lower amount of biofilm and formed less root nodules compared to the wild-type strain with Phaseolus vulgaris as host plant. Finally, expression of the operon containing bceN was induced by the presence of germinated P. vulgaris seeds under nitrogen limiting conditions suggesting a role of this polysaccharide in the establishment of this ecologically important symbiosis.